Напрями удосконалення механізму державного управління у сфері освіти і науки в контексті необхідності інноваційного розвитку України - Майстро, Сергій Вікторович; Майстро, Руслана Григорівна (My University, 2018)
Визначено сучасний стан та результативність механізму державного управління у сфері освіти і науки в Україні, виділено його основні проблеми та протиріччя. Означено основні напрями вдосконалення механізму державного управління у сфері освіти і науки в контексті необхідності інноваційного розвитку України.

The present state and efficiency of the mechanism of public administration in the field of education and science in Ukraine is determined. The main problems and contradictions of the mechanism of public administration in the field of education and science in Ukraine are highlighted. The main directions of improvement of the mechanism of public administration in the field of education and science in the context of the need for innovative development of Ukraine are identified.
Areas of improvement of the mechanism of public administration in the field of education and science in the context of the need for innovative development of Ukraine
Keywords: економіка; конкурентні переваги; інформаційні технології; навчальний процес; міжнародна співпраця; mechanism of state administration; economics; innovative development